2013
DOI: 10.1177/1756283x13482996
|View full text |Cite
|
Sign up to set email alerts
|

Role of the gut microbiota in health and chronic gastrointestinal disease: understanding a hidden metabolic organ

Abstract: Abstract:The human gut microbiota has become the subject of extensive research in recent years and our knowledge of the resident species and their potential functional capacity is rapidly growing. Our gut harbours a complex community of over 100 trillion microbial cells which influence human physiology, metabolism, nutrition and immune function while disruption to the gut microbiota has been linked with gastrointestinal conditions such as inflammatory bowel disease and obesity. Here, we review the many signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
447
0
16

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 681 publications
(495 citation statements)
references
References 111 publications
3
447
0
16
Order By: Relevance
“…The variation in these factors for each individual may give rise to functional redundancy in gut microbiota, which results in diversity among individuals in the gut inhabitants, having the same role of keeping the normal gut functioning in each individual. Greater variations are usually encountered at deeper taxonomic levels rather than at phylum level [18]. …”
Section: The Gut Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…The variation in these factors for each individual may give rise to functional redundancy in gut microbiota, which results in diversity among individuals in the gut inhabitants, having the same role of keeping the normal gut functioning in each individual. Greater variations are usually encountered at deeper taxonomic levels rather than at phylum level [18]. …”
Section: The Gut Microbiotamentioning
confidence: 99%
“…Environmental factors such as host genetics, ageing, health, lifestyle, early colonization, use of antibiotics and diet can affect the diversity and composition of the gut microbiota [18,26]. However, the gut microbiota generally has a remarkable innate ability to resist such exposures and disturbances, a property known as resilience; therefore, the microbial community is usually drawn back to its original state before the disturbance [17,27].…”
Section: The Gut Microbiotamentioning
confidence: 99%
“…Because previous studies revealed the close relationship between the composition of gut microbiota and metabolic diseases, inflammation, or colon cancer (18,19), we further investigated how gut microbiota have changed upon Prohep feeding during the HCC development. The taxonomy profiles at the genus level revealed that the gut bacteria community in the mice was dominated by Bacteroidetes (49% on average), Firmicutes (37% on average), and Proteobacteria (4.5% on average) (Fig.…”
Section: Probiotics Mediate the Structural And Functional Compositionmentioning
confidence: 99%
“…As a consequence of the controversial and unresolved role of Blastocystis in human intestinal disease and the increased awareness of the importance of the gut microbiome (and specific components of the gut microbiome) in human health and disease, research into Blastocystis has increased greatly in recent years (Andersen and Stensvold, 2015;Guinane and Cotter, 2013;Roberts et al, 2014;Scanlan, 2012;Scanlan and Stensvold, 2013;Sekirov et al, 2010). Although the application of sensitive molecular PCR based techniques has faciltated a better appreciation of the prevalence of Blastocystis in human populations, there remains a lack of reliable epidemiological data on the prevalence and genetic diversity of Blastocystis from many regions of the world including the United States.…”
Section: Introductionmentioning
confidence: 99%